Relationship between Risk Factors for Dug Well Contamination with Total Coliform Counts in Dug Well Water - Elisa Tri Yulianti; Arum Siwiendrayanti (Universitas Diponegoro, 2024)
Dug well water can be a source of disease transmission if contaminated by pathogenic bacteria. Many people in Purworejo Regency still use dug wells as a source of drinking water. This secondary data study aims to determine the risk factors associated with total coliform counts in dug well water in the working area of the Purworejo District Health Office in 2022. Cross sectional research design and data analysis techniques chi square test with fisher alternative test. The population was 61 dug wells that had been carried out Environmental Health Inspections on Household Drinking Water Quality Study data and a sample of 53 dug wells. The research was conducted in August-October 2022. The results showed an association between the risk factors of well wall condition (p value = 0.041) and well cover (p value = 0.048) to the total number of dug well coliforms. It is recommended to the local community to improve the physical condition of dug wells, especially well walls and well covers so that contaminating substances from outside the well do not enter and contaminate dug well water.